Harvest time in the seed quality of soybean genotypes - Xavier, Thiago da Silva Xavier; Daronch, Douglas; Peluzio, Joênes Muci; Afférri, Flávio Sérgio; de Carvalho, Edmar Vinícius; dos Santos, Weder Ferreira (Comunicata Scientiae, 2015)
With the objective to evaluate the seeds quality of soybean genotypes at different harvest times, it was conducted a field experiment at the experimental farm at Universidade Federal do Tocantins in Gurupi – TO, in the season 2010/2011. The experimental design was completely randomized blocks with fifty treatments and three repetitions. The treatments were arranged in a factorial design and they were represented by ten cultivars (BRS ValiosaRR, M8527RR, P98Y51, TMG103RR, P98Y70, M8867RR, M8925RR, TMG115RR, M9056RR and M9144RR) and five harvest times (R8, R8+7, R8+14, R8+21 and R8+28 days). They were realized the following tests: standard germination and germination in sand, with four repetitions of 50 seed for each treatment, that were obtained from the field experiment, and the experimental design was completely randomized. With the delay in the harvest was verified the progressive reduction of germination in all cultivars, from seven days after the R8 stage. The cultivar M9056RR has shown the higher quality seeds.